A High-Throughput Metabolic Microarray Assay Reveals Antibacterial Effects of Black and Red Raspberries and Blackberries against Helicobacter pylori Infection - Candace Goodman; Katrina N. Lyon; Aitana Scotto; Cyra Smith; Thomas A. Sebrell; Andrew B. Gentry; Ganesh Bala; Gary D. Stoner; Diane Bimczok (MDPI AG, 2021)
Helicobacter pylori infection is commonly treated with a combination of antibiotics and proton pump inhibitors. However, since H. pylori is becoming increasingly resistant to standard antibiotic regimens, novel treatment strategies are needed. Previous studies have demonstrated that black and red berries may have antibacterial properties. Therefore, we analyzed the antibacterial effects of black and red raspberries and blackberries on H. pylori. Freeze-dried powders and organic extracts from black and red raspberries and blackberries were prepared, and high-performance liquid chromatography was used to measure the concentrations of anthocyanins, which are considered the major active ingredients. To monitor antibiotic effects of the berry preparations on H. pylori, a high-throughput metabolic growth assay based on the Biolog system was developed and validated with the antibiotic metronidazole. Biocompatibility was analyzed using human gastric organoids. All berry preparations tested had significant bactericidal effects in vitro, with MIC90 values ranging from 0.49 to 4.17%. Antimicrobial activity was higher for extracts than powders and appeared to be independent of the anthocyanin concentration. Importantly, human gastric epithelial cell viability was not negatively impacted by black raspberry extract applied at the concentration required for complete bacterial growth inhibition. Our data suggest that black and red raspberry and blackberry extracts may have potential applications in the treatment and prevention of H. pylori infection but differ widely in their MICs. Moreover, we demonstrate that the Biolog metabolic assay is suitable for high-throughput antimicrobial susceptibility screening of H. pylori.